A Spanish version of the Ramak Interest Inventory - Peiser, Carlos; Meir, Elchanan I. (Revista Interamericana de Psicología/Interamerican Journal of Psychology, 2017)
A Spanish interest inventory was built, based on Roe’s (1956) classification of occupations. Following positive results on a Hebrew version -Ramak- it consists of 72 occupational titles of “Y” ? “N” scale.